Antitumor effect and mechanism of FZD7 polypeptide vaccine - Hua, Zhongke; Han, Yu; Liu, Kan; Yang, Hua; Zhou, Cai; Chen, Fengyi; Nie, Shenglan; Li, Mengqing; Yu, Qinyao; Wei, Yunpeng; Wu, Christina C. N.; Wang, Xiaomei (Frontiers in Oncology, 2022)
The resistant cells that proliferate after radiotherapy and chemotherapy are primarily tumor stem cells with high stem marker expression, and their presence is the primary cause of tumor dispersion. The Wnt signaling receptor Frizzled family receptor 7 (FZD7) is linked to the maintenance of stem cell features as well as cancer progression. Frizzled-7 (FZD7), a key receptor for Wnt/-catenin signaling, is overexpressed in TNBC, suggesting that it could be a viable target for cancer therapy. We employed bioinformatics to find the best-scoring peptide, chemically synthesized FZD7 epitope antigen, and binding toll-like receptor 7 agonists (T7). Under GMP conditions, peptides for vaccines were produced and purified (>95%). In vivo and vitro tests were used to assess tumor cell inhibition. In vitro, the FZD7-T7 vaccination can boost the maturity of BMDC cells considerably. In mice, the FZD7 - T7 vaccine elicited the greatest immunological response. Significant tumor development inhibition was seen in BALB/c mice treated with FZD7 - T7 in prevention experiments (P < 0.01). Multiple cytokines that promote cellular immune responses, such as interferon (IFN)-γ (P < 0.05), interleukin (IL)-12 (P < 0.05), and IL-2 (P < 0.01), were shown to be considerably elevated in mice inoculated with FZD7- T7. Furthermore, we evaluated safety concerns in terms of vaccine composition to aid in the creation of successful next-generation vaccines. In conclusion, the FZD7-T7 vaccine can activate the immune response in vivo and in vitro, and play a role in tumor suppression. Our findings reveal a unique tumor-suppressive role for the FZD7 peptide in TNBC.